2020
DOI: 10.1039/d0ra00687d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient extraction of aromatic amines in the air by the needle trap device packed with the zirconium based metal–organic framework sorbent

Abstract: Development of a needle trap device (NTD) packed with UiO-66 adsorbent was used for the sampling of the aromatic amine compounds (including aniline, N,N-dimethylaniline and o-toluidine) followed by gas chromatography (GC) with flame-ionization detector (FID) analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Besides, the potential functionalization and post-modification of MOFs have exposed the art of chemists in different fields 15,16 . The various documents have been reported for synthesis and electrosynthesis of MOFs as powder and thin films [17][18][19][20][21][22][23][24][25][26][27][28][29] . Behind the beneficial chemical synthesis procedures, the anodic and cathodic electrosynthesis methods are easy to observe and have been received a more acceptable niche and platform because of the environmentally friendly conditions [30][31][32][33][34] .…”
mentioning
confidence: 99%
“…Besides, the potential functionalization and post-modification of MOFs have exposed the art of chemists in different fields 15,16 . The various documents have been reported for synthesis and electrosynthesis of MOFs as powder and thin films [17][18][19][20][21][22][23][24][25][26][27][28][29] . Behind the beneficial chemical synthesis procedures, the anodic and cathodic electrosynthesis methods are easy to observe and have been received a more acceptable niche and platform because of the environmentally friendly conditions [30][31][32][33][34] .…”
mentioning
confidence: 99%
“…However, unlike SPME method, the NTD is considered an active sampling method, which is based on using a personal sampling pump. 13,16 NTD involves packing a specic amount of absorbent inside a small needle, enabling the trapping and qualitative/quantitative iden-tication of analytes in air samples. NTDs are inexpensive, robust, reusable, and suitable for single-step sampling [13][14][15][16][17][18][19][20][21][22] and analysis of Volatile Organic Compounds (VOCs) from different matrices.…”
Section: Introductionmentioning
confidence: 99%
“… 12 In another study, the reported RSD for intermediate precision using an NTD packed with the UIO-66 adsorbent for sampling aromatic hydrocarbons from the air was estimated to be less than 14.3%. 41 Moreover, this parameter was reported to be less than 6.5% for the sampling of the halogenated hydrocarbons in urine samples by the HS-SPME method coupled with a fiber coated with the Al 2 O 3 –TiO 2 composite. 9 Therefore, it can be concluded that the proposed needle trap sampler offers satisfactory repeatability and intermediate precision results for commercialization.…”
Section: Resultsmentioning
confidence: 99%